Educational Technology and the Future of Learning from a Global Perspective - Mustaji; Sulisworo, Dwi; Maimunah; Diningrat, Syaiputra Wahyuda Meisa (Buletin Edukasi Indonesia, 2025)
Technological advancements are transforming education worldwide, offering new opportunities to enhance accessibility and learning quality. This article examines global trends such as AI-driven personalized learning, online and hybrid models, gamification, and immersive technologies like AR and VR. While these innovations offer benefits, including broader access and skill development, challenges persist, such as digital divides, data security, and teacher training gaps. To address these issues, strategies like investing in digital infrastructure, integrating technology into curricula, and fostering global collaboration are proposed. Educational technology has the potential to create inclusive and future-ready learning systems, provided challenges are met with coordinated efforts.